ENERGY SECURITY AND SUSTAINABILITY IN THE WESTERN BALKANS: CHALLENGES ON THE PATH TOWARD GREEN TRANSITION - Vukadinovic, Marija (Political Review, 2026)
Energy security, as an essential dimension of national security, is deeply intertwined with economic, social, and geopolitical dynamics and represents one of the most pressing challenges facing the Western Balkan region at both national and supranational levels. At the national level, energy security is strongly connected to political stability and economic resilience, while at the supranational level, it is tied to the region’s ongoing process of European integration. The Western Balkans face a complex and interdependent set of challenges in achieving energy security and sustainability, situated within the broader context of the European Union’s Green Deal and the Green Agenda for the Western Balkans. This paper examines the evolving relationship between energy security, environmental sustainability, and regional cooperation, noting how certain structural and institutional limitations within the Western Balkan countries may slow the pace of the green transition. The study identifies key vulnerabilities in national energy systems while assessing the degree of alignment with EU climate objectives and the 2050 carbon neutrality target. The findings reveal that despite modest improvements in renewable energy integration, the Western Balkan region remains highly dependent on fossil fuels, particularly coal, and vulnerable to fluctuations in energy imports, which together hinder progress toward decarbonization and long-term stability. Strengthening regional cooperation mechanisms, alongside transparent and predictable regulatory frameworks, emerges as a prerequisite for advancing both energy security and sustainability. The paper concludes that achieving the 2050 climate neutrality objective will remain highly challenging for the Western Balkans unless regional cooperation is significantly strengthened and aligned with broader European efforts.